Peningkatan Kemampuan Pemahaman Membaca Teks Narrative Bahasa Inggris Melalui Penerapan Media Vidio Terhadap Peserta Didik Kelas XI IPS2 SMAN Negeri 5 Bukittinggi - Syahrial, Wenny (CV. ITTC INDONESIA, 2022)
This study aims to improve the ability to read English narrative texts by applying video media to students of class XI IPS2 at SMA Negeri 5 Bukittingi. This study applies video media in teaching narrative text. The population of this study were students of class XI IPS2 SMA Negeri 5 Bukittinggi for the 2021/2022 academic year, which consisted of 33 students. This Classroom Action Research is expected to improve students' reading comprehension skills in English narrative texts. The findings of Classroom Action Research (PTK) after being analyzed showed that based on the initial scores of students in class XI IPS2 semester 1, they obtained an average score of 53. After the first cycle was carried out, the average value was 67.6 and after the second cycle was carried out, it increased to 84.5. . From the initial data, it can be seen from the 33 students, 2 students obtained completeness, namely 6.06% and 31 students did not achieve completeness, namely 93.9%. In cycle 1, students who obtained mastery increased by 8 people, namely (24.2%) and 25 students who had not achieved mastery, namely 75.7%. In cycle 2 the students who obtained mastery increased to 31 students namely (93.9%) and 2 students who had not achieved completeness namely 6.06%. reading narrative texts in English for class XI IPS2 students at SMA Negeri 5 Bukittinggi.